Prinsip Pemuridan Menurut Kisah Para Rasul 2:42 Bagi Pertumbuan Rohani Jemaat Masa Kini - Hermanto, Abang (Sekolah Tinggi Teologi Immanuel Sintang Kal-Bar, 2022)
This article discusses the discipleship principle in Acts 2:42 for the spiritual growth of the church today as seen in the output in Acts 2:47. This study aims to explain the principles of discipleship that are relevant for the spiritual growth of the church today, by studying the principles found in Acts. Researchers use qualitative research methods and a biblical approach. This principle focuses on the apostles' teaching, fellowship, breaking bread, and prayer as means of deepening understanding of Christ's doctrine. The guiding principles used by followers of Jesus Christ at that time included several important elements. First, the direct teaching of the apostles became the main foundation of learning. This emphasizes the importance of having teachers who provide proper teaching. Second, fellowship becomes an important element in learning. Followers of Christ learn from others through discussion, brainstorming, and helping each other understand the doctrine of Christ. Third, breaking bread becomes a significant learning method. During this activity, followers of Christ discuss and deepen their understanding of Christ's doctrine. This activity creates strong social bonds between members of the congregation and allows for mutual strengthening in faith. Fourth, prayer is an important aspect of this learning method. Followers of Christ learn through prayer and strengthen faith through prayer together.